The Antecedents And Consequences Of Trust In Online Retail - Marisa Fitria Andika; Luki Adiati Pratomo; Sisca Damayanti (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
This study examines the antecedents and consequences of trust in online retail in the area of Jabodetabek. Samples were consumers who have shopped at online retail (Tokopedia), totaling 200 respondents. They were selected using the non-probability sampling method with a purposive sampling technique. The collected data were analyzed using Structural Equation Modeling. Results indicated that the complementary of interaction quality, complementary of environment quality, and complementary of outcome quality have a positive effect on trust in the retailer. Likewise, trust in the retailer has a positive effect on the intention to recommendations.